Bilirubin as a potential causal factor in type 2 diabetes risk: a Mendelian randomization study - Abbasi, Ali; Deetman, Petronella E; Corpeleijn, Eva; Gansevoort, Ron T; Gans, Rijk O B; Hillege, Hans L; van der Harst, Pim; Stolk, Ronald P; Navis, Gerjan; Alizadeh, Behrooz Z; Bakker, Stephan J L (Diabetes (New York, N.Y.), 2015)
Circulating bilirubin, a natural antioxidant, is associated with decreased risk of type 2 diabetes (T2D), but the nature of the relationship remains unknown. We performed Mendelian randomization in a prospective cohort of 3,381 participants free of diabetes at baseline (age 28-75 years; women 52.6%). We used rs6742078 located in the uridine diphosphate-glucuronosyltransferase locus as an instrumental variable (IV) to study a potential causal effect of serum total bilirubin level on T2D risk. T2D developed in a total of 210 participants (6.2%) during a median follow-up period of 7.8 years. In adjusted analyses, rs6742078, which explained 19.5% of bilirubin variation, was strongly associated with total bilirubin (a 0.68-SD increase in bilirubin levels per T allele; P < 1 × 10(-122)) and was also associated with T2D risk (odds ratio [OR] 0.69 [95% CI 0.54-0.90]; P = 0.006). Per 1-SD increase in log-transformed bilirubin levels, we observed a 25% (OR 0.75 [95% CI 0.62-0.92]; P = 0.004) lower risk of T2D. In Mendelian randomization analysis, the causal risk reduction for T2D was estimated to be 42% (causal OR for IV estimation per 1-SD increase in log-transformed bilirubin 0.58 [95% CI 0.39-0.84]; P = 0.005), which was comparable to the observational estimate (Durbin-Wu-Hausman χ(2) test, P for difference = 0.19). These novel results provide evidence that an elevated bilirubin level is causally associated with the risk of T2D and support its role as a protective determinant.